Green low-carbon laser-weldable absorbing layer glass fiber reinforced nylon composite material and preparation method thereof

By using low-carbon nylon materials, intrinsic viscosity nylon resin and treated glass fiber and other raw materials, combined with laser flux and additives, a green, low-carbon laser welding absorption layer glass fiber reinforced nylon composite material is prepared, solving the existing solutions The material cannot meet the low-carbon environmental protection requirements, achieving efficient and precise laser welding effects and material performance improvements.

CN119391171APending Publication Date: 2025-02-07HENAN TIANHAI HEJU NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411618496.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing laser welding composite materials cannot meet the requirements of low-carbon and environmental protection, and it is difficult to achieve efficient and precise welding effects during laser welding.

Method used

Using low-carbon nylon materials, nylon resin with intrinsic viscosity, glass fibers with coupling agent surface treatment, near-infrared absorption laser flux and additives, the green low-carbon laser welding absorption layer glass fiber is prepared through the twin-screw extrusion mechanism. Reinforced nylon composite material.

Benefits of technology

It realizes the preparation of low-carbon and environmentally friendly composite materials, meets the absorption layer requirements of laser welding, maintains the mechanical properties of more than 85% of the brand new material, and improves the welding strength and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391171A_ABST
    Figure CN119391171A_ABST
Patent Text Reader

Abstract

The invention provides a green low-carbon laser-weldable absorbing layer glass fiber reinforced nylon composite material and a preparation method thereof, and belongs to the technical field of high polymer material processing, the green low-carbon laser-weldable absorbing layer glass fiber reinforced nylon composite material comprises the following raw materials: a low-carbon nylon material, nylon resin, glass fiber, a laser scaling powder, an auxiliary agent and a black dye. The invention provides a green low-carbon laser-weldable absorbing layer glass fiber reinforced nylon composite material and a preparation method thereof. The absorbing layer composite material which is low-carbon and environment-friendly and meets the laser welding requirement is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material processing, and in particular to a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material and a preparation method thereof. Background Art

[0002] With the continuous improvement and development of scientific and technological innovation, the automotive production field has put forward higher and higher requirements for automobile lightweight and automobile body art aesthetics. Traditional plastic welding, hot plate welding, vibration friction welding, ultrasonic welding and other processes can no longer meet these requirements. As a non-contact, efficient and precise welding method, laser welding technology has outstanding advantages such as excellent processing, stable product quality and high work efficiency, and is gradually favored by the automotive processing and welding field.

[0003] At present, the basic requirements for laser welding are: the laser must penetrate the upper light-transmitting layer, and the lower absorption layer must have a strong absorption capacity for laser energy. After absorbing enough laser radiation energy, the absorption layer at the weld is converted into heat energy to melt the absorption layer material, and at the same time, the heat is transferred to the light-transmitting layer at the weld to melt it. Under the action of the continuous support force applied between the upper and lower layers, the upper and lower molten materials are well fused, making the weld fit tightly. After cooling and solidification, the strength of the welding area will be very close to the strength of the material itself, thus forming a whole with uniform performance.

[0004] Publication number CN117659690A, titled "A nylon 66 composite material, its preparation method and application", is disclosed as follows: in parts by weight, the nylon 66 composite material includes 25-62 parts of nylon 66 resin, 13-54 parts of flat glass fiber, 10-20 parts of halogen-free flame retardant and 5.5-10 parts of synergistic flame retardant; the halogen-free flame retardant is an inorganic hypophosphite; the synergistic flame retardant includes a combination of non-cage polysiloxane and cage polysilsesquioxane; the viscosity of the nylon 66 resin is less than or equal to 3.0. By compounding the components, the nylon 66 composite material has the advantages of high laser transmittance, good flame retardant performance and less precipitation under high temperature and high humidity conditions, and is particularly suitable for electronic components prepared by laser welding technology. However, with the promotion of the concept of low-carbon and environmentally friendly development, automobile production OEMs have also put forward new requirements for automobile production materials, and the composite materials in the above technical scheme cannot meet the requirements of low-carbon and environmental protection. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material, so as to achieve the preparation of a low-carbon, environmentally friendly absorption layer composite material that meets laser welding requirements.

[0006] To achieve the above object, the present invention provides a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material, the raw materials of the composite material comprising: low-carbon nylon material, nylon resin, glass fiber, laser flux, additives and black dye; The low-carbon nylon material is any one or a combination of two or more of nylon 66 recycled material and bio-based nylon 56; The nylon resin includes any one or a combination of two of nylon 66 / nylon 6 copolymer resin with an intrinsic viscosity of 2.62-2.75 dL / g, nylon 66 resin with an intrinsic viscosity of 2.45-2.8 dL / g, and nylon 6 resin with an intrinsic viscosity of 2.45-2.8 dL / g; The laser soldering flux is any one of near-infrared absorbing laser powder and near-infrared absorbing laser masterbatch or a combination of both.

[0007] Optionally, the glass fiber is short glass fiber that has been surface treated with a coupling agent.

[0008] The glass fiber provided by the present invention is short glass fiber surface-treated with a coupling agent, which can enhance the bonding ability with the resin and improve the strength and rigidity of the composite material.

[0009] Optionally, the auxiliary agents include a heat-resistant agent, a high-temperature-resistant lubricant and an anti-floating fiber agent.

[0010] Optionally, the heat-resistant agent is any one of an organic copper salt heat-resistant agent, an inorganic copper salt heat-resistant agent and an amine heat-resistant agent, or a combination of two or more thereof.

[0011] The heat-resistant agent provided by the present invention can effectively inhibit the degradation of materials caused by excessive processing, prevent the breakage of polymer molecular chains by absorbing heat, keep the molecular structure unchanged, and can also inhibit oxygen in the air to prevent oxidation of materials, further improving the performance and service life of composite materials.

[0012] Optionally, the high temperature resistant lubricant is any one of silicone, pentaerythritol stearate and E wax, or a combination of two or more thereof.

[0013] Optionally, the anti-fiber floating agent is any one of a hyperbranched anti-fiber floating agent, a TAF anti-fiber floating agent and a SEED anti-fiber floating agent, or a combination of two or more thereof.

[0014] The high temperature resistant lubricant and anti-floating fiber agent in the present invention help to improve the dispersibility and compatibility of glass fiber in resin, prevent the "floating fiber" phenomenon, thereby improving the mechanical properties of the composite material and making the product prepared from the composite material have a good appearance.

[0015] Optionally, the black dye is any one of carbon black, carbon black masterbatch and aniline black masterbatch, or a combination of two or more thereof.

[0016] Optionally, the composite material includes the following raw materials in weight percentage: 25% to 35% low-carbon nylon material, 30% to 40% nylon resin, 10% to 30% glass fiber, 0.2% to 1.0% laser flux, 0.3% to 0.8% heat resistant agent, 0.3% to 0.8% high temperature resistant lubricant, 0.3% to 0.8% anti-floating fiber agent and 0.5% to 2.0% black dye.

[0017] In order to achieve the above-mentioned purpose, the present invention also provides a method for preparing a green, low-carbon, laser-weldable, glass-fiber-reinforced nylon composite material with an absorption layer, comprising the following steps: weighing raw materials, drying low-carbon nylon material and nylon resin, premixing the dried low-carbon nylon material and nylon resin in a high-speed mixer to obtain an initial mixed material, mixing the initial mixed material, a heat-resistant agent, a laser flux, a high-temperature resistant lubricant, an anti-floating fiber agent and a black dye in the high-speed mixer to obtain a secondary mixed material; adding the secondary mixed material from a main feed port and conveying it to a screw cavity of a twin-screw extruder, adding the glass fiber from a side feed port and conveying it to the screw cavity of the twin-screw extruder, heating and melting in the screw cavity, extruding granulation, and screening to obtain a green, low-carbon, laser-weldable, glass-fiber-reinforced nylon composite material with an absorption layer.

[0018] Optionally, the conditions for drying the low-carbon nylon material and the nylon resin are as follows: a drying temperature of 80-100° C. and a drying time of 4-6 hours; and the heating and melting temperature in the screw cavity is 250-280° C.

[0019] The above technical solution of the present invention includes at least the following beneficial effects: The present invention provides a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material, comprising: low-carbon nylon material, nylon resin, glass fiber, laser flux, additives and black dye; the low-carbon nylon material used in this application is waste or unqualified modified nylon material generated during the injection molding process, or bio-based nylon 56 prepared from biomass materials, and then mixed with nylon resin of a specific viscosity, so that the low-carbon nylon material and the nylon resin form an integral structure, and the composite material is filled and reinforced by glass fiber to improve the mechanical properties of the composite material. The nylon material and the nylon resin are also combined with additives and laser flux to improve the dispersibility of the glass fiber in the nylon resin, so that the composite material can be used as an absorption layer for laser welding for laser welding. The particularity of the low-carbon nylon material in the raw material not only reduces the production cost, but also reduces the carbon emissions in the production process. The prepared composite material can maintain more than 85% of the mechanical properties of the new material and meet the requirements of laser welding. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1The present invention is a flow chart of preparing a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the following will be combined with the appended drawings of the embodiments of the present invention. Figure 1 , the technical scheme of the embodiment of the present invention is clearly and completely described. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0022] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods.

[0023] In the embodiments of the present invention, the intrinsic viscosity of the nylon 66 / nylon 6 copolymer resin is 2.62-2.75 dL / g, the intrinsic viscosity of the nylon 66 resin is 2.45-2.8 dL / g, and the intrinsic viscosity of the nylon 6 resin is 2.45-2.8 dL / g.

[0024] Example 1 The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material of this embodiment includes the following raw materials in percentage by weight: Nylon 66 recycled material 30wt% Nylon 66 / Nylon 6 copolymer resin 36.6wt% Glass fiber 30wt% Laser powder 0.3wt% Organic copper salt heat resistant agent 0.5wt% Silicone 0.5wt% Hyperbranched anti-floating agent 0.6wt% Carbon black masterbatch 1.5wt% In this embodiment, the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material is prepared by the following steps: (1) Weigh the raw material components according to the above formula; (2) Dry the raw low-carbon nylon material and nylon resin in an oven at 80°C for 6 hours; (3) premixing the dried low-carbon nylon material and nylon resin in a high-speed mixer to obtain an initial mixed material; (4) Mixing the initial mixed material, laser flux, heat resistant agent, high temperature resistant lubricant, anti-floating agent and carbon black masterbatch in a high-speed mixer to obtain a secondary mixed material; (5) The secondary mixed material is added from the main feed port and conveyed into the screw cavity of the twin-screw extruder, and the glass fiber is added from the side feed port and conveyed into the screw cavity of the twin-screw extruder, heated and melted in the screw cavity, and the heating and melting temperature is 250°C. The mixed material is extruded into granules and sieved to obtain a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material.

[0025] Example 2 The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material of this embodiment includes the following raw materials in percentage by weight: Nylon 66 recycled material 30wt% Nylon 66 resin 26.6wt% Nylon 6 resin 10wt% Glass fiber 30wt% Laser masterbatch 0.3wt% Inorganic copper salt heat resistant agent 0.5wt% E wax 0.5wt% TAF anti-floating agent 0.6wt% Carbon black 1.5wt% In this embodiment, the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material is prepared by the following steps: (1) Weigh the raw material components according to the above formula; (2) Dry the raw low-carbon nylon material and nylon resin in an oven at 100°C for 4 hours; (3) premixing the dried low-carbon nylon material and nylon resin in a high-speed mixer to obtain an initial mixed material; (4) mixing the initial mixed material, laser flux, heat resistant agent, high temperature resistant lubricant, anti-floating agent and carbon black in a high-speed mixer to obtain a secondary mixed material; (5) The secondary mixed material is added from the main feed port and conveyed into the screw cavity of the twin-screw extruder, and the glass fiber is added from the side feed port and conveyed into the screw cavity of the twin-screw extruder, heated and melted in the screw cavity, and the heating and melting temperature is 280°C. The mixed material is extruded into granules and sieved to obtain a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material.

[0026] Example 3 The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material of this embodiment includes the following raw materials in percentage by weight: Bio-based nylon 5630wt% Nylon 66 / Nylon 6 copolymer resin 36.6wt% Glass fiber 30wt% Laser powder 0.3wt% Amine heat resistant agent 0.5wt% Pentaerythritol stearate 0.5wt% SEED anti-floating agent 0.6wt% Aniline black masterbatch 1.5wt% The preparation method of the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material in this embodiment is consistent with that in Example 1.

[0027] Example 4 The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material of this embodiment includes the following raw materials in percentage by weight: Bio-based nylon 5630wt% Nylon 66 resin 26.6wt% Nylon 6 resin 10wt% Glass fiber 30wt% Laser masterbatch 0.3wt% Inorganic copper salt heat resistant agent 0.5wt% E wax 0.5wt% TAF anti-floating agent 0.6wt% Carbon black 1.5wt% The preparation method of the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material in this embodiment is consistent with that in Example 1.

[0028] Comparative Example 1 The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material in this comparative example includes the following raw materials in percentage by weight: Nylon 66 / Nylon 6 copolymer resin 66.6wt% Glass fiber 30wt% Laser powder 0.3wt% Organic copper salt heat resistant agent 0.5wt% Silicone 0.5wt% Hyperbranched anti-floating agent 0.6wt% Carbon black masterbatch 1.5wt% The preparation method of the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material in this embodiment is consistent with that in Example 3.

[0029] Comparative Example 2 The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material of this comparative example includes the following raw materials in percentage by weight: Nylon 66 resin 56.6wt% Nylon 6 resin 10wt% Glass fiber 30wt% Laser masterbatch 0.3wt% Inorganic copper salt heat resistant agent 0.5wt% E wax 0.5wt% TAF anti-floating agent 0.6wt% Carbon black 1.5wt% The preparation method of the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material in this embodiment is consistent with that in Example 4.

[0030] In the present application, the materials prepared in Examples 1-4 and Comparative Examples 1-2 are used as the absorption layer for laser welding, and the light-transmitting layer material is a nylon 66+GF30 composite material, and the material of the light-transmitting layer includes the following components by weight fraction: Nylon 66 resin 58.4wt% Nylon 6 resin 10wt% Glass fiber 30wt% Heat resistant agent 0.5wt% High temperature resistant lubricant 0.5wt% Anti-floating agent 0.6wt% The preparation method of the light-transmitting layer material is the same as that of Example 1.

[0031] The performance tests were conducted on the composite materials and the materials of the light-transmitting layer prepared in Examples 1-4 and Comparative Examples 1-2 of the present invention. The test results are shown in Table 1 below: Table 1 Test results

[0032] As can be seen from the above table, the density of the absorption layer materials used in Examples 1-4 and Comparative Examples 1-2 is consistent with that of the light-transmitting layer, and the mechanical properties are basically similar. After laser melting, it is more conducive to forming a whole. After adding different types of low-carbon nylon materials and nylon resins, Examples 1-4 can achieve mechanical properties of more than 85% of the performance of the comparative material, and do not affect the welding strength of the material during laser welding, indicating that low-carbon nylon materials can replace new nylon resins and become the matrix resin of composite materials, and the prepared composite materials can be used in the automotive field, providing a direction for automotive precision welding.

[0033] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material, characterized in that: The raw materials of the composite material include: low-carbon nylon material, nylon resin, glass fiber, laser flux, additives and black dye; The low-carbon nylon material is any one or a combination of nylon 66 recycled material and bio-based nylon 56; The nylon resin includes any one or a combination of two or more of nylon 66 / nylon 6 copolymer resin with an intrinsic viscosity of 2.62 to 2.75 dL / g, nylon 66 resin with an intrinsic viscosity of 2.45 to 2.8 dL / g, and nylon 6 resin with an intrinsic viscosity of 2.45 to 2.8 dL / g; The laser soldering flux is any one of near-infrared absorbing laser powder and near-infrared absorbing laser masterbatch or a combination of both.

2. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 1, characterized in that: The glass fiber is short glass fiber surface-treated with a coupling agent.

3. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 1, characterized in that: The auxiliary agents include heat-resistant agents, high-temperature-resistant lubricants and anti-floating fiber agents.

4. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 3, characterized in that: The heat-resistant agent is any one of an organic copper salt heat-resistant agent, an inorganic copper salt heat-resistant agent and an amine heat-resistant agent, or a combination of two or more thereof.

5. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 3, characterized in that: The high temperature resistant lubricant is any one of silicone, pentaerythritol stearate and E wax or a combination of two or more thereof.

6. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 3, characterized in that: The anti-fiber floating agent is any one of a hyperbranched anti-fiber floating agent, a TAF anti-fiber floating agent and a SEED anti-fiber floating agent, or a combination of two or more thereof.

7. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 1, characterized in that: The black dye is any one of carbon black, carbon black masterbatch and aniline black masterbatch or a combination of two or more thereof.

8. The green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 7, characterized in that: The composite material comprises the following raw materials in weight percentage: 25% to 35% of low-carbon nylon material, 30% to 40% of nylon resin, 10% to 30% of glass fiber, 0.2% to 1.0% of laser soldering flux, 0.3% to 0.8% of heat-resistant agent, 0.3% to 0.8% of high-temperature resistant lubricant, 0.3% to 0.8% of anti-floating fiber agent and 0.5% to 2.0% of black dye.

9. A method for preparing a green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed, and the low-carbon nylon material and the nylon resin are dried. The dried low-carbon nylon material and the nylon resin are pre-mixed in a high-speed mixer to obtain an initial mixed material. The initial mixed material, a heat-resistant agent, a laser flux, a high-temperature resistant lubricant, an anti-floating fiber agent and a black dye are mixed in the high-speed mixer to obtain a secondary mixed material. The secondary mixed material is added from a main feed port and conveyed into a screw cavity of a twin-screw extruder, and the glass fiber is added from a side feed port and conveyed into the screw cavity of the twin-screw extruder. The glass fiber is heated and melted in the screw cavity, extruded into granules, and sieved to obtain a green, low-carbon, laser-weldable, absorbing layer glass fiber reinforced nylon composite material.

10. The method for preparing the green, low-carbon, laser-weldable absorption layer glass fiber reinforced nylon composite material according to claim 9, characterized in that: The conditions for drying the low-carbon nylon material and the nylon resin are as follows: a drying temperature of 80-100° C. and a drying time of 4-6 hours; and a heating and melting temperature in the screw cavity of 250-280° C.